2022
DOI: 10.3389/fgene.2022.937639
|View full text |Cite
|
Sign up to set email alerts
|

The association of MTHFR (rs1801133) with hypertension in an indigenous south African population

Abstract: Aims: The current study sought to investigate the association between the methylenetetrahydrofolate reductase (MTHFR) variant (rs1801133) and the risk of developing hypertension (HTN) in an indigenous South African population.Methods: A total of 442 participants (hypertensive, n = 279 and non-hypertensive, n = 163) from the indigenous tribe residing in Mthatha, Eastern Cape (South Africa) were recruited. HTN was defined as a systolic (SBP) and diastolic blood pressure (DBP) of ≥130/80 mmHg following American H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…For instance, the T allele was associated with a higher risk of hypertension in Taiwanese ( 48 ), Chinese ( 47 , 50 , 77 ), Indians ( 78 ), and Australian Caucasians ( 52 ), and the TT genotype in Moroccans ( 51 ). Nonetheless, the variant was not significantly associated with hypertension in Algerians ( 79 ), South Africans ( 80 ), Chinese ( 54 , 81 ), Danish ( 53 ), Caucasians ( 55 ), Japanese ( 56 ), Black Africans ( 76 ), Latinos ( 76 ), Sri Lankans ( 76 ), and Indians ( 76 ). We believe that the conflicting results between our study and those previously reported could, in part, be due to differences in ethnicities, sample sizes, and study designs.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, the T allele was associated with a higher risk of hypertension in Taiwanese ( 48 ), Chinese ( 47 , 50 , 77 ), Indians ( 78 ), and Australian Caucasians ( 52 ), and the TT genotype in Moroccans ( 51 ). Nonetheless, the variant was not significantly associated with hypertension in Algerians ( 79 ), South Africans ( 80 ), Chinese ( 54 , 81 ), Danish ( 53 ), Caucasians ( 55 ), Japanese ( 56 ), Black Africans ( 76 ), Latinos ( 76 ), Sri Lankans ( 76 ), and Indians ( 76 ). We believe that the conflicting results between our study and those previously reported could, in part, be due to differences in ethnicities, sample sizes, and study designs.…”
Section: Discussionmentioning
confidence: 95%
“…TT genotype is associated with EH in a Moroccan population. [34] To date, no genetic association with EH has been described in South African cohorts [18,35,36], though genetic associations in distinct South African ethnic groups have been described with blood pressure traits [37,38] and uncontrolled hypertension [16,39,40].…”
Section: Nos3mentioning
confidence: 99%
“…To date, no genetic association with EH has been described in South African cohorts [ 18 , 35 , 36 ], though genetic associations in distinct South African ethnic groups have been described with blood pressure traits [ 37 , 38 ] and uncontrolled hypertension [ 16 , 39 , 40 ]. South Africa, with its rich ethnic diversity [ 41 , 42 , 43 ], presents a unique opportunity to unearth ethnic-specific associations, shedding light on the complex interplay between genetics and EH.…”
Section: Introductionmentioning
confidence: 99%